PENGEMBANGAN MEDIA PEMBELAJARAN CLAWS BOX PELAJARAN MATEMATIKA MATERI BANGUN RUANG DAN BANGUN DATAR DI KELAS II SDN PLUMBUNGAN - Elis Indah Saraswati; Rikke Kurniawati (Jurnal Muassis Pendidikan Dasar, 2022)
This research is conducted to solve the problems that exist in the second grade students of SDN Plumbungan Sukodono Sidoarjo. The purpose of this study was to develop an interesting Claws Box learning media at Plumbungan Sukodono Elementary School, Sidoarjo. This type of research is development research. The method used by this researcher uses the ADDIE development model. Data collection techniques uses in this study were validation of material development and validation of development media development and validation of lesson plans development. The stages carried out by the researchers consist of three stages, namely: Analysis. Design and Development. The result of the assessment from the material expert validator showed a percentage score of 87% which was categorized as “Very Valid”. While the results of the media assesments developed by researchers have been validated by media expert validators with a percentage score of 81% which is categorized as “Very Valid”. As well as the results of the assessment of the RPP expert validators showed a percentage score of 75% which was categorized as “Valid”. This Shows that the Claws Box media is feasible to use in the learning process